Constitutional modernization and effectiveness of constitutional justice in Uzbekistan: institutional and procedural decisions - Adam, Ye.; Beibitov, M.S.; Mukhamedzhanov, O.Z. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article is devoted to the study of modern areas of increasing the efficiency of the Constitutional Court of the Republic of Uzbekistan in the context of the constitutional modernization of 2023. Based on the analysis of regulatory sources, judicial practice and comparative legal material, new proposals have been formulated to improve the status and procedural instruments of the Constitutional Court, which go beyond the previously proposed measures. The research revealed such problems of the functioning of the court as limited procedural access of citizens and courts of lower level, the lack of temporary interim measures and an effective mechanism for the execution of decisions, insufficient involvement of external expertise, as well as a shortage of personnel and analytical resources. This study justifies the need for legislative consolidation of the right of the Constitutional Court to temporarily suspend the contested norms pending a decision on the merits, the introduction of a package of measures related to the deferred loss of force of acts recognized as unconstitutional and mandatory execution procedures. It is proposed to institutionalize the participation of external experts (amicus curiae), introduce a pilot constitutional resolution procedure to eliminate repeated structural violations, and create a digital platform for an open register of decisions with neutral quotes and execution statistics. Additionally, the expediency of publishing a dissenting opinion of judges, the formation of a stable budget and personnel base for the independence of the court, as well as the introduction of a mandatory constitutional certificate for each bill and algorithmic monitoring of regulations for compliance with the Constitution. The implementation of the proposed measures will make it possible to transfer the Constitutional Court of Uzbekistan to a proactive model that ensures preliminary constitutional control, strengthens institutional independence, and increases public confidence in constitutional justice.